3D-Printing Piezoelectric Composite with Honeycomb Structure for Ultrasonic Devices - Yushun Zeng; Laiming Jiang; Yizhe Sun; Yang Yang; Yi Quan; Shuang Wei; Gengxi Lu; Runze Li; Jiahui Rong; Yong Chen; Qifa Zhou (Micromachines, 2020)
Piezoelectric composites are considered excellent core materials for fabricating various ultrasonic devices. For the traditional fabrication process, piezoelectric composite structures are mainly prepared by mold forming, mixing, and dicing-filing techniques. However, these techniques are limited on fabricating shapes with complex structures. With the rapid development of additive manufacturing (AM), many research fields have applied AM technology to produce functional materials with various geometric shapes. In this study, the Mask-Image-Projection-based Stereolithography (MIP-SL) process, one of the AM (3D-printing) methods, was used to build BaTiO3-based piezoelectric composite ceramics with honeycomb structure design. A sintered sample with denser body and higher density was achieved (i.e., density obtained 5.96 g/cm3), and the 3D-printed ceramic displayed the expected piezoelectric and ferroelectric properties using the complex structure (i.e., piezoelectric constant achieved 60 pC/N). After being integrated into an ultrasonic device, the 3D-printed component also presents promising material performance and output power properties for ultrasound sensing (i.e., output voltage reached 180 mVpp). Our study demonstrated the effectiveness of AM technology in fabricating piezoelectric composites with complex structures that cannot be fabricated by dicing-filling. The approach may bring more possibilities to the fabrication of micro-electromechanical system (MEMS)-based ultrasonic devices via 3D-printing methods in the future.